Implementation of Integrated Services at Al-Aqsha Modern Islamic Boarding School, Jatinangor, Sumedang - Wisnu Uriawan; Agung Harliyadi Imam Dhuhuri; Aditya Nur Rohman (al-Afkar, Journal For Islamic Studies, 2025)
This study aims to analyze the implementation of the One Stop Integrated Service (PTSP) system at Pondok Modern Al-Aqsha Jatinangor in improving the quality of education services, administration. This research uses a qualitative method with a field study approach, involving observation, in-depth interviews, and documentation of the Pondok Modern Al-Aqsha leadership, Public Relations staff and asatidz. The results showed that the implementation of PTSP at Pondok Modern Al-Aqsha has succeeded in simplifying the previously fragmented service process to be more integrated and efficient with the pesantren's public relations as a service and information center. Administrative, financial, and academic services can now be accessed centrally through one channel, which not only increases time efficiency but also improves the quality of interaction between the pesantren and service users. The implementation of PTSP has had a positive impact in increasing operational efficiency, strengthening service transparency, and improving the image of pesantren as a modern educational institution that is responsive to community needs.